2020
DOI: 10.1371/journal.pone.0239342
|View full text |Cite
|
Sign up to set email alerts
|

Blinded rechecking of sputum smear microscopy performance in public health facilities in Tigray region, Northern Ethiopia: Retrospective cross sectional study

Abstract: Introduction Tuberculosis disease is the leading cause of death worldwide along with HIV/AIDS. Sputum smear microscopy plays an essential role for initial TB diagnosis and treatment follow up. But, misdiagnosis of sputum smear microscopy revealed a high economical crisis and missing of active TB cases. This study was aimed to determine blinded rechecking of sputum smear microscopy performance in public health facilities in Tigray region, Northern Ethiopia. Materials and methods A cross sectional retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This study has shown that EQA-blind rechecking participation practice for AFB-Microscopy was 52.9% among Xpert® MTB/RIF testing health facilities. This finding is similar to the northern part of Ethiopia’s that showed participating decreased from time to time which indicates there should be a re-vitalization of the EQA-blind rechecking practice in the country [ 46 ]. Regarding the on-site supervision practice, on-site supervision was not well practiced in TB-culture laboratories (33.3%).…”
Section: Discussionsupporting
confidence: 69%
“…This study has shown that EQA-blind rechecking participation practice for AFB-Microscopy was 52.9% among Xpert® MTB/RIF testing health facilities. This finding is similar to the northern part of Ethiopia’s that showed participating decreased from time to time which indicates there should be a re-vitalization of the EQA-blind rechecking practice in the country [ 46 ]. Regarding the on-site supervision practice, on-site supervision was not well practiced in TB-culture laboratories (33.3%).…”
Section: Discussionsupporting
confidence: 69%
“…In frequency of laboratory errors, six papers [18][19][20][21][22][23] were looked at specific major technical laboratory errors. Shiferaw et al, 18 showed that 47 of 201 (23.4%) laboratories in the study had major false positive and false negative errors in diagnosing tuberculosis.…”
Section: Frequency Of Laboratory Errorsmentioning
confidence: 99%
“…Similarly, Mekonen et al 19 showed that 20 of 55 (36.4%) health center laboratories had false positive and false negative results in diagnosing tuberculosis. In addition, Desalegn et al 20 Measuring with some indicators like smear size, specimen quality, smear thickness, smear evenness and smear cleanliness, Weldemhret et al 21 showed that the performance of sputum smear quality were 68%, 61, 64%, 62 and 66% respectively. On the other hand, Tadesse et al study 22 showed that 742 of 2606 (28.5%) hematology laboratory specimens in the study had different technical errors.…”
Section: Frequency Of Laboratory Errorsmentioning
confidence: 99%
“…A number of factors, including social disparities in health, a lack of qualified local healthcare providers, and inadequate healthcare infrastructure in resource-constrained and developing nations, pose obstacles to efforts to reduce or eradicate this communicable disease. Therefore, it is clear that creating cost-effective mechanisms is an extremely important issue for medical treatment ( 3 ). Early diagnosis, effective treatment (therapy) are important ways to reduce the rate of the spread of this communicable disease (TB).…”
Section: Introductionmentioning
confidence: 99%
“…Chest x-rays or smear microscopy are almost exclusively used methods for research on automated TB system diagnosis. In terms of usability, accessibility, and maintainability, the sputum smear microscopic detection method for tuberculosis is the gold standard ( 3 , 6 , 7 ). To the best of the author's current knowledge, there is no research work conducted to assess sputum smears quality or Tb detection and diagnosis using CNN, SVM, and KNN classifiers.…”
Section: Introductionmentioning
confidence: 99%